Exploring Infant Caregivers' Provision of Modified Formulas: Potential Demographic Differences and Reasons for Provisions - Gershman, Haley; Romo-Palafox, Maria J.; Rajeh, Tassneem; Fleming-Milici, Frances; Harris, Jennifer L. (Frontiers in Nutrition, 2022)
Background. Formula brands have modified the ingredients in standard infant formulas and extensively market modified formulas, claiming benefits for infants that are not supported by scientific evidence. This exploratory study examined the proportion of infant caregivers who reported serving modified formula, demographic differences, and reasons for providing them. Methods. Cross-sectional online survey of U.S. caregivers of infants (6-11 months) who provided formula in the past month (N=436). Participants reported the type of formula served most often and agreement with potential reasons for provision. Logistic regression assessed odds of serving modified formula by demographic differences. MANOVA examined differences in agreement with purchase reasons between caregivers by type of formula provided. Results. Approximately one-half (47%) of participants reported serving modified formula most often; sensitive and organic/non-GMO were the most common types provided. Caregivers in the middle-income group were most likely to serve modified formulas; but provision did not differ by other demographic characteristics. Agreement with reasons for providing was highest for "pediatricians recommend" and "benefits for my child" (M=4.2 out of 5). Agreement with "my pediatrician prescribed" and "natural ingredients" were significantly higher for modified versus standard formula providers. Conclusions. Widespread provision of modified formula by infant caregivers raises concerns due to its higher cost and lack of scientific evidence supporting benefits for babies. These finding suggest regulations limiting unsubstantiated formula claims and restrictions on misleading marketing to consumers are necessary. Additional research is needed to understand pediatricians' perceptions of modified formulas and reasons for recommending them to patients.